A ground-to-GEO-to-LEO satellite optical wireless communication link based on a spectrally efficient and secure modulation scheme - Xu, Chen; Khan, Umair Ali; Ghafoor, Salman; Mirza, Jawad; Aljohani, Abdulah Jeza; Aziz, Imran (Frontiers in Physics, 2025)
Optical wireless communication (OWC) offers significant advantages over traditional radio frequency systems due to its high bandwidth, ease of deployment, license-free operation, immunity to electromagnetic interference, and inherent security benefits. This research presents a novel all-optical technique for transmitting multiple data channels over an optical link, employing Differential Phase-Shift Keying (DPSK) and Pulse Position Modulation (PPM) schemes. Notably, the combination of DPSK and PPM enhances both data security and spectral efficiency compared to conventional methods. The proposed technique demonstrably achieves error-free transmission of three data channels, each at a data rate of 10 Gbps, as validated through simulation results. Furthermore, the study explores the applicability of this technique to inter-satellite links. By integrating with a geostationary Earth orbit (GEO) data relay satellite, this technique can improve link availability for low-Earth orbit (LEO) satellites. Our novel approach holds significant promise for practical deployment and seamless integration into future high-speed and secure communication networks, catering to the ever-growing demand for robust data transmission.